2020
DOI: 10.17533/udea.iee.v38n1e10
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Gender inequalities around Informal Care

Abstract: This work comes from the interest and need to understand the problems arising from the activity of caring for dependent people, in the world and particularly in the European region. Altogether, it seeks to understand the consequences of informal care on the caregiver adding to the debate a gender perspective. Through a multidisciplinary bibliographic review, the current care crisis becomes clear. The demographic and socio-cultural changes in recent years are causing dependency to increase dramatically, while p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…The caregivers in the CuidaCare study were mostly women (72.8%), married (82.8%), without an education or with a primary education (72.4%), and who had always dedicated to domestic work (47.2%). This socioeconomic profile is consistent with the reports in the literature and similar to data from our region [ 15 , 18 , 19 , 31 , 32 , 34 , 39 , 40 ]. Our study found a slightly higher proportion of male caregivers (27.2%) than has been reported in other studies.…”
Section: Discussionsupporting
confidence: 93%
“…The caregivers in the CuidaCare study were mostly women (72.8%), married (82.8%), without an education or with a primary education (72.4%), and who had always dedicated to domestic work (47.2%). This socioeconomic profile is consistent with the reports in the literature and similar to data from our region [ 15 , 18 , 19 , 31 , 32 , 34 , 39 , 40 ]. Our study found a slightly higher proportion of male caregivers (27.2%) than has been reported in other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Followed by shorter duration of the mental disorder, and having greater internalized stigma. The model has female gender as the main and strongest predictor, again identifying women as a vulnerable group, and perhaps supporting studies on the impact of violence on women and the consequences for their mental health ( Oram et al., 2017 ); the negative effect of the burden of informal care ( Cascella Carbó and García-Orellán, 2020 ); and the impact of discrimination on women's mental health ( Hackett et al., 2019 ). This last argument is particularly remarkable because of the presence of internalized stigma as a predictor variable, previously demonstrated as a variable related to poorer mental health and symptomatology ( Del Rosal et al., 2020 ).…”
Section: Discussionsupporting
confidence: 65%
“…This may partly be because women perceive the demands of caregiving more intensely than men [ 32 , 33 ]. In fact, the literature has consistently shown that greater caregiving burden among women is associated with lower societal recognition of the value of their work and deep-seated gender norms that leave them with little freedom to make decisions on what their role should be [ 34 ]. These social expectations mean that women experience the pressure of caregiving more than men and this has a greater impact on their health and other aspects of their life [ 35 ].…”
Section: Discussionmentioning
confidence: 99%